Gender equality policies, nursing professionalization, and the nursing workforce: A cross-sectional, time-series analysis of 22 countries, 2000–2015. (November 2019) - Gunn, Virginia; Muntaner, Carles; Ng, Edwin; Villeneuve, Michael; Gea-Sanchez, Montserrat; Chung, Haejoo
Abstract: Background: Nursing professionalization has substantial benefits for patients, health care systems, and the nursing workforce. Currently, however, there is limited understanding of the macro-level factors, such as policies and other country-level determinants, influencing both the professionalization process and the supply of nursing human resources. Objectives: Given the significance of gender to the development of nursing, a majority-female occupation, the purpose of this analysis was to investigate the relationship between gender regimes and gender equality policies, as macro-level determinants, and nursing professionalization indicators, in this case the regulated nurse and nurse graduate ratios. Design: This cross-sectional, time-series analysis covered 16 years, from 2000 to 2015, and included 22 high-income countries, members of the Organisation for Economic Co-operation and Development. We divided countries into three clusters, using the gender policy model developed by Korpi, as proxy for gender regimes. The countries were grouped as follows: (a) Traditional family — Austria, Belgium, France, Germany, Greece, Italy, Netherlands, Portugal, and Spain; (b) Market-oriented — Australia, Canada, Ireland, Japan, New Zealand, South Korea, Switzerland, United Kingdom, and the United States; and (c) Earner-carer — Denmark, Finland, Norway, and Sweden. Methods: We used fixed-effects linear regression models and ran Prais-Winsten regressions with panel-corrected standard errors, including a first-order autocorrelation correction to examine the effect of gender equality policies on nursing professionalization indicators. Given the existence of missing observations, we devised and implemented a multiple imputation strategy, with the help of the Amelia II program. We gathered our data from open access secondary sources. Results: Both the regulated nurse and nurse graduate ratios had averages that differed across gender regimes, being the highest in Earner-carer regimes and the lowest in Traditional family ones. In addition, we identified a number of indicators of gender equality policy in education, the labour market, and politics that are predictive of the regulated nurse and nurse graduate ratios. Conclusion: This study's findings could add to existing upstream advocacy efforts to strengthen nursing and the nursing workforce through healthy public policy. Given that the study consists of an international comparative analysis of nursing, it should be relevant to both national and global nursing communities.